GROWTH AND YIELD OF SHALLOT UNDER SEVERAL LEVELS OF SOIL WATER TABLE - Susilawati; Irmawati; Sukarmi S.; Ammar M.; Kurnianingsih A.; Yusnita; Yayandra (Russian Journal of Agricultural and Socio-Economic Sciences, 2021)
The research was aimed to evaluate differences on growth and yield of two shallot varieties under several levels of soil water table. It was conducted in experimental field and plastic house of Agriculture Faculty, Universitas Sriwijaya for three months in 2019. Materials used were shallot bulb from Tajuk and Pancasona varieties and biochar originated from oil palm empty fruit bunch. Factorial Randomized Block Design was used with two treatment factors and three replicates. First treatment was 2 shallot variety consisting Tajuk and Pancasona variety. Second treatment was level of soil water table including T0= 0 cm below soil surface; T1= 10 cm below soil surface; T2= 15 cm below soil surface; and T3= 20 cm below soil surface. The observed parameters consisted of plant height, leaf number, tiller number, total bulb fresh weight, bulb fresh weight, bulb dry weight, bulb number, bulb diameter, and root length. Results showed that shallot growth of Pancasona and Tajuk variety was highly affected by levels of soil water table. It was then concluded that Pancasona variety showed better growth performance and yield compared to Tajuk variety. The deeper soil water table reaching 20 cm below soil surface can reduce growth and yield of shallot.